PFOA promotes PMAIP1–MCL1 apoptotic vulnerability within a BHLHE41-associated macrophage regulatory architecture in atherosclerosis - Hou-liang Chen; Run Wang; Wei-jun Tao; Wang Zhang; Yan-lin Gao; Xiao-bing Cheng (Chemico-Biological Interactions, 2026)

Iridoids from the edible flowers of Rhododendron pachypodum: structural elucidation and healthspan related bioactivities in Caenorhabditis elegans - Ying Wang; Hou-Run Zhang; Jie Luan; Qi Cheng; Bing Chen; Xiang-Qin Tang; Xiao-Mei Yan; Yong-Ming Yan; Jiang-Bo He (Phytochemistry, 2026)

An unprecedented alternariol-zinnol hybrid and six undescribed zinnol derivatives from the phytopathogen Alternaria solani and their cytotoxic activities - Ming Hu; Run-Cheng Yan; Qiao-Ling Wei; Jiang-Li Su; Bi-Juan Yang; Wen-Chao Tu; Gan-Peng Li; Xing-De Wu (Phytochemistry, 2026)

Cassane diterpenoids with hepatic gluconeogenesis inhibitory activity from the seeds of Caesalpinia decapetala (Roth) Alston - De-Sheng Wang; Yu Shen; Lin-Fen Ding; Run-Cheng Yan; Ming Hu; Wen-Chao Tu; Liu-Dong Song; Suling Huang; Xing-De Wu (Phytochemistry, 2025)

A study on soil erodibility and the applicability of estimation methods in Robinia pseudoacacia L. mixed forests on the Loess Plateau, China - Jin-long Ma; Bing Wang; Run-hao Yu; Yan-fen Yang; Guo-bin Liu; Jing Wang; Cheng-fang Li (CATENA, 2025)

Integrated network pharmacology, bioinformatics, and experiment analysis to decipher the molecular mechanism of Salidroside on Gastric cancer via targeting NCOA4-mediated ferritinophagy - Yu Fu; Guiqin Huang; Yawen Cai; Menghui Ren; Run Cheng; Yuhui Chai; Yingdi Wang; Yunqi An; Tianhua Yan; Lingpeng Zhu; Xinxin Liu (Chemico-Biological Interactions, 2025)

Structurally diverse diterpenoids from the seeds of Caesalpinia minax Hance and their bioactivities - Wen-Chao Tu; Lin-Fen Ding; Liu-Dong Song; Yong-Jiao Li; Run-Cheng Yan; Yun Wu; Wei-Yang Feng; Xing-De Wu (Phytochemistry, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

Anti-pancreatic cancer activity of cassane diterpenoids isolated from the seeds of Caesalpinia sappan mediated by autophagy activation via ROS/AMPK/mTORC1 pathway - Jia Su; De-Sheng Wang; Guo-Xian Hu; Yu-Yao Liu; Ming Hu; Ya Chen; Qi-Qi Wang; Run-Cheng Yan; Yun Wu; Yong-Jiao Li; Ke Ma; Yan-Yan Qi; et al. (Phytochemistry, 2024)

Identification, distribution, bactericidal and immunoregulatory activities of NK-lysins in grass carp (Ctenopharyngodon idella) - Gai Ling Wang; En Zhong Li; Da Hong Li; Ming Cheng Wang; Shan Shan Sun; Run Yan Xiong; Chuan Feng Li; Bao Jian Sun; Hai Xia Xie (Aquaculture, 2024)

Green N1 additive modified perovskite precursor enables effective manufacturing of large-area solar cell modules with high efficiency and stability - Yue Zang; Yibo Tu; Chuanjia Jiao; Wangnan Li; Peng Zhou; Jiahao Cheng; Gaoyuan Yang; Tianxiang Shao; Jingchuan Ye; Guodong Li; Liang Chu; Shaojian Lu; et al. (Chemical Engineering Journal, 2024)

LC-MS Based Metabolomic Profiling of Largehead Hairtail (Trichiurus japonicus) Ovary Reveals Metabolic Signatures of Ovarian Developmental Process (II–IV) - Liu-Ying Feng; Li-Ping Yan; Run-Wei Li; Sheng-Fa Li; Jia-Hua Cheng; Yan Jin (Fishes, 2023)
Trichiurus japonicus is an economically important fish that ranks 11th in global marine fish capture production. However, the reproductive characteristics of this fish have undergone notable changes in recent decades, potentially affecting the quality of offspring and sustainable utilization. To improve our understanding of the physiological regulation of maturation in T. japonicus, untargeted liquid chromatography mass spectrometry was utilized to identify the small molecules that characterize the comprehensive metabolic profiles of ovaries during ovary development from stage II to stage IV. According to the results of OPLS-DA, the ovarian metabolite profiles of the three developmental stages were separated. The concentrations of 124 and 100 metabolites were significantly altered between stage II vs. III and III vs. IV, respectively. Lipids and lipid-like molecules accounted for the largest proportion of the altered metabolites, followed by amino acids, peptides, and analogues. The significantly altered metabolites-enriched pathways differed slightly between stages II and III and stages III and IV. Steroid-related pathways were heavily affected during stages II to III, while significantly altered metabolites from stages III to IV were involved in oocyte-maturation-related pathways. Through metabonomics analysis, potentially important metabolic pathways and metabolites between different ovarian stages were detected, providing basic information for further investigation of maturation mechanisms in wild fish.

Trophinin-associated protein expression correlates with shorter survival of patients with glioma: a study based on multiple data fusion analysis - Yong Sun; Zhen Dong Liu; Run Ze Liu; Xiao Yu Lian; Xing Bo Cheng; Yu Long Jia; Bin Feng Liu; Yan Zheng Gao; Xinjun Wang (Molecular Biology Reports, 2022)

Identification and functional characterization of a PDR transporter in Tripterygium wilfordii Hook.f. that mediates the efflux of triptolide - Guopeng Miao; Juan Han; Yan-bo Huo; Cheng-run Wang; Shun-chang Wang (Plant Molecular Biology, 2021)

Gastroprotective effect of palmatine against acetic acid-induced gastric ulcers in rats - Ling Wang; Xue Wang; Su-Li Zhang; Xiao-Ming Zhu; Yan-Qi Liu; Zi-Jing Song; Wen-Juan Du; Jun Ji; Cheng-Long Cui; Xin He; Chun-Feng Zhang; Chang-Run Guo; et al. (Journal of Natural Medicines, 2017)

RT-PCR test for detecting porcine sapovirus in weanling piglets in Hunan Province, China - Guo-Hua Liu; Run-Cheng Li; Ze-Bin Huang; Jun Yang; Chao-Ting Xiao; Jing Li; Man-Xiang Li; Yun-Qiu Yan; Xing-Long Yu (Tropical Animal Health and Production, 2012)

An efficient three-component, one-pot synthesis of 2-alkylthio-4-amino-5-cyano-6-aryl(alkyl)pyrimidines in water - Qiao-Yan Li; Ze-Mei Ge; Tie-Ming Cheng; Run-Tao Li (Molecular Diversity, 2012)